Contribution of Informed Reference Prior Using Primary and Summary Measure Data in Bayesian Meta-Analysis - Soni, Most Sifat Muntaha; Hossain, Md Belal (Dhaka University Journal of Science, 2015)
When meta-analysis includes a small number of trials, inferences are sensitive to the choice of prior distributions for between-study heterogeneity. The common practice is to use vague prior but inferences depend on the degree of vagueness. Pullenayegum (2011) proposed an informed reference prior for between-study heterogeneity of binary outcomes. We employ a model for applying this prior for both primary outcome and summary measure data in Bayesian meta-analysis. We have found the same inference using both primary outcome and summary measure data. This study also suggests that the informed reference prior for between-study heterogeneity represents more relevant conclusion as compared to commonly used prior distributions. Dhaka Univ. J. Sci. 63(2): 61-65, 2015 (July)